The dynamics of two-party politics party structures and the management of competition - Ware, Alan.; European Consortium for Political Research (Oxford : Oxford University Press, 2009)
This book examines the role played by the parties themselves in two-party systems. It rejects the argument that the behaviour of the parties is determined largely by social forces or by the supposed logic of the electoral market. Instead, it shows that both structure and agency can matter.
Published in association with the European Consortium for Political Research.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Two-party systems; Comparative government